Monitoring the disassembly of virus-like particles by (19)F-NMR - Leung, R; Robinson, M; Ajabali, A; Karunanithy, G; Lyons, B; Raj, R; Raoufmoghaddam, S; Mohammed, S; Claridge, T; Baldwin, A; Davis, B (American Chemical Society, 2017)
Virus-like particles (VLPs) are stable protein cages derived from virus coats. They have been used extensively as biomolecular platforms, e.g., nanocarriers or vaccines, but a convenient in situ technique is lacking for tracking functional status. Here, we present a simple way to monitor disassembly of (19)F-labeled VLPs derived from bacteriophage Qβ by (19)F NMR. Analysis of resonances, under a range of conditions, allowed determination not only of the particle as fully assembled but also as disassembled, as well as detection of a degraded state upon digestion by cells. This in turn allowed mutational redesign of disassembly and testing in both bacterial and mammalian systems as a strategy for the creation of putative, targeted-VLP delivery systems.